2004
DOI: 10.1074/jbc.m312709200
|View full text |Cite
|
Sign up to set email alerts
|

The CCAAT Enhancer-binding Protein α (C/EBPα) Requires a SWI/SNF Complex for Proliferation Arrest

Abstract: The transcription factor CCAAT enhancer-binding protein ␣ (C/EBP␣) is a tumor suppressor in myeloid cells and inhibits proliferation in all cell types examined. C/EBP␣ interacts with the SWI/SNF chromatinremodeling complex during the regulation of differentiation-specific genes. Here we show that C/EBP␣ fails to suppress proliferation in SWI/SNF defective cell lines after knock-down of SWI/SNF core components or after deletion of the SWI/SNF interaction domain in C/EBP␣, respectively. Reconstitution of SWI/SNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 59 publications
3
66
0
Order By: Relevance
“…Potential antagonistic protein interactions leading to a block in C/EBPa function in AML have been well implicated in recent findings (Pabst et al, 2001a;Vangala et al, 2003;Zheng et al, 2004). Interestingly, C/EBPa also functions via direct proteinprotein interactions in normal stem cell development (Behre et al, 2002a;D'Alo et al, 2003;Muller et al, 2004); PU.1 and c-Jun inactivation (Rangatia et al, 2002;Reddy et al, 2002), E2F repression (Porse et al, 2001), and cdk2 and cdk4 inhibition (Wang et al, 2001) by C/EBPa are all accompanied by direct protein-protein interactions. Moreover, different protein partners of C/EBPa in young and old mice livers itself demonstrate the importance of protein-protein interactions during ageing (Iakova et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Potential antagonistic protein interactions leading to a block in C/EBPa function in AML have been well implicated in recent findings (Pabst et al, 2001a;Vangala et al, 2003;Zheng et al, 2004). Interestingly, C/EBPa also functions via direct proteinprotein interactions in normal stem cell development (Behre et al, 2002a;D'Alo et al, 2003;Muller et al, 2004); PU.1 and c-Jun inactivation (Rangatia et al, 2002;Reddy et al, 2002), E2F repression (Porse et al, 2001), and cdk2 and cdk4 inhibition (Wang et al, 2001) by C/EBPa are all accompanied by direct protein-protein interactions. Moreover, different protein partners of C/EBPa in young and old mice livers itself demonstrate the importance of protein-protein interactions during ageing (Iakova et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…7). TAD4 is known to be essential for direct binding of C/EBP-TAD to the TAF2B and TBP components of the general RNA polymerase II transcriptional apparatus (70) and also for interaction of C/EBP␤ with CBP and p300 transcriptional coactivators and SWI/SNF chromatin remodeling factors (73)(74)(75)(76)(77). Thus, GADD45␤ activation of C/EBP␤-TAD4 function via MTK1/MKK3/6/p38 signaling suggests a general mechanism for facilitating processes driven by transcription factors containing TAD4-like domains, such as c-Jun (72).…”
Section: Gadd45␤ Regulation Of Genes Involved In Terminal Chondrocytementioning
confidence: 99%
“…Among them, the SWI/ SNF complexes, which consist of one or more catalytic subunits: Brahma (Brm), Brahma-related gene 1 protein (Brg1) or Breastovarian cancer susceptibility protein 1 (Brca1), and polycomb repressors (Bmi-1), play roles in neural development. Muller et al found that the SWI/SNF complexes were also associated with the cell differentiation and cell cycle arrest mediated by C/EBP [38] .…”
Section: Chromatin Remodelingmentioning
confidence: 99%
“…Among them, the SWI/ SNF complexes, which consist of one or more catalytic subunits: Brahma (Brm), Brahma-related gene 1 protein (Brg1) or Breastovarian cancer susceptibility protein 1 (Brca1), and polycomb repressors (Bmi-1), play roles in neural development. Muller et al found that the SWI/SNF complexes were also associated with the cell differentiation and cell cycle arrest mediated by C/EBP [38] .The SWI/SNF complexes interact with HATs or HDACs and/or sequence-specific transcription factors to activate or repress the target genes. Kondo et al suggest that the conversion of oligodendrocyte precursor cells to neural-stem-like cells is associated with recruitment of the Brca1 and Brm (the catalytic subunit in a subset of SWI/ SNF) to the promoter of a key transcription factor gene Sox2, which involves in maintaining the proliferation of NSCs [39] by methylation at K4 and acetylation at K9 in the histone H3 of the promoter.…”
mentioning
confidence: 99%